2022
DOI: 10.3390/ijerph19159110
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study on the Association of Lead, 8-Hydroxyguanine, and Malondialdehyde Levels in Opium Addicts’ Blood Serum with Illicit Drug Use and Non-Addict Persons

Abstract: While a large body of literature has shown the health problems of illicit drug use, research is needed on how substance abuse impacts DNA damage and contaminants in blood, especially given Pb-contaminated opium. This pilot study aimed to evaluate the levels of lead (Pb), 8-hydroxy di-guanine (8-oxo-Gua), and malondialdehyde (MDA) in the blood serum of opium addicts and non-addict people. The current study is a case–control study with a cross-sectional design. A sample of 50 opium-addicted and non-addict adults… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…The FDA and the CDC recommend an Interim Reference Level of 12.5 μg/day for adults [ 8 ]. Studies have revealed that even lower levels of lead (Pb) concentration thresholds can have adverse effects, such as cognitive, neurobehavioral, and neurophysiological disorders, as well as impairment of learning ability and intelligence, especially in children [ 7 , [9] , [10] , [11] ]. Lead poisoning can also induce oxidative stress, leading to alteration in gene expression associated with reactive oxygen species (ROS), resulting in serious, irreversible damage to the gastrointestinal (GI), hematological, reproductive, immunological, renal, and hepatic systems [ [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%
“…The FDA and the CDC recommend an Interim Reference Level of 12.5 μg/day for adults [ 8 ]. Studies have revealed that even lower levels of lead (Pb) concentration thresholds can have adverse effects, such as cognitive, neurobehavioral, and neurophysiological disorders, as well as impairment of learning ability and intelligence, especially in children [ 7 , [9] , [10] , [11] ]. Lead poisoning can also induce oxidative stress, leading to alteration in gene expression associated with reactive oxygen species (ROS), resulting in serious, irreversible damage to the gastrointestinal (GI), hematological, reproductive, immunological, renal, and hepatic systems [ [12] , [13] , [14] , [15] ].…”
Section: Introductionmentioning
confidence: 99%